2019
DOI: 10.1016/j.scitotenv.2019.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of high spatial resolution surface air temperature data across China: A new geo-intelligent multisource data-based machine learning technique

Abstract: Good knowledge of the surface air temperature (SAT) is critical for scientific understanding of ecological environment changes and land-atmosphere thermodynamic interactions. However, sparse and uneven spatial distribution of the temperature gauging stations introduces remarkable uncertainties into analysis of the SAT pattern.From a geo-intelligent perspective, here we proposed a new SAT reconstruction method based on the multisource data and machine learning technique which was developed by considering autoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Machine learning has shown remarkable potential in geosciences in recent years for various applications such as land use change detection, precipitation prediction and bias-correcting forecast [17][18][19]. Deep learning methods have made revolutionary advances in the sequential data-modeling domain [20][21][22][23][24] or for streamflow forecasting [25]. Recently, several studies have used the so-called hybrid modeling approach, coupling physical-models with machine learning [20,21,26].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has shown remarkable potential in geosciences in recent years for various applications such as land use change detection, precipitation prediction and bias-correcting forecast [17][18][19]. Deep learning methods have made revolutionary advances in the sequential data-modeling domain [20][21][22][23][24] or for streamflow forecasting [25]. Recently, several studies have used the so-called hybrid modeling approach, coupling physical-models with machine learning [20,21,26].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we just directly add geo-coordinates (longitude and latitude) and time information (day of the year) into the feature space as that done in other studies (e.g. [52] [53] [54] [55] [56] [57] [58]). In total, we selected 11 variables as the candidate features based on our domain knowledge.…”
Section: Feature Selectionmentioning
confidence: 99%
“…The authors showed that adding these covariates improved prediction and produced results that mimic kriging. Zhu et al [25] proposed an ML model which considers autocorrelation to reconstruct surface air temperature data at high spatial resolution across China. They added weights based on altitude and distance differences between the target station and surrounding stations as covariates.…”
Section: Introductionmentioning
confidence: 99%